The Endocannabinoids-Microbiota Partnership in Gut-Brain Axis Homeostasis: Implications for Autism Spectrum Disorders - Coccurello, Roberto; Marrone, Maria Cristina; Maccarrone, Mauro (Frontiers in Pharmacology, 2022)
The latest years have witnessed a growing interest towards the relationship between neuropsychiatric disease in children with autism spectrum disorders (ASD) and severe alterations in gut microbiota composition. In parallel, an increasing literature has focused the attention towards the association between derangement of the endocannabinoids machinery and some mechanisms and symptoms identified in ASD pathophysiology, such as alteration of neural development, immune system dysfunction, defective social interaction and stereotypic behavior. In this narrative review, we put together the vast ground of endocannabinoids and their partnership with gut microbiota, pursuing the hypothesis that the crosstalk between these two complex homeostatic systems (bioactive lipid mediators, receptors, biosynthetic and hydrolytic enzymes and the entire bacterial gut ecosystem, signaling molecules, metabolites and short chain fatty acids) may disclose new ideas and functional connections for the development of synergic treatments combining “gut-therapy,” nutritional intervention and pharmacological approaches. The two separate domains of the literature have been examined looking for all the plausible (and so far known) overlapping points, describing the mutual changes induced by acting either on the endocannabinoid system or on gut bacteria population and their relevance for the understanding of ASD pathophysiology. Both human pathology and symptoms relief in ASD subjects, as well as multiple ASD-like animal models, have been taken into consideration in order to provide evidence of the relevance of the endocannabinoids-microbiota crosstalk in this major neurodevelopmental disorder.